Role of Climatic Conditions on the Incidence of Varicella in an Out-patient Clinic of a Tertiary Care Pediatric Hospital at Dhaka (Ibrahim Cardiac Medical Journal, 2021)
Background & objective : Chicken pox or varicella is a disease of both tropical and temperate zones bearing a complex-relationship with climatic variables, like temperature, rainfall and relative humidity, wind velocity and so on. As no study has, by far, been conducted to relate its occurrence with these climatic variables in Bangladesh, this study was intended to explore the effect of weather conditions on the incidence of varicella in Dhaka city of Bangladesh.Methods: The present cross-sectional study obtained data of 172 varicella cases from the records of the daily register of Out-patient Department of Dhaka Shisu Hospital, Dhaka between January 2018 to December 2019. According to the study protocol a child was diagnosed as having varicella or chicken pox who had a history of short febrile illness accompanied by a pruritic vesicular eruption (on the face and trunk)) of the skin and mucous membranes which ultimate weeps out and crusts. Total number of cases treated monthly at Out-patient Department (OPD) during the period was also recorded. Climatic data were provided by Bangladesh Meteorological Department, which among others, included monthly average temperature, relative humidity (RH) and amount of rainfall or precipitation. While the outcome variable was monthly number of varicella cases, the predictive variables were average temperature, humidity and rainfall during the study period.Result: Over 70% of children were 1-10 years old with median age of the children being 5.5 years (range: < 1 month -14 years). Boys were a bit higher (54%) than the girls (46%). A seasonal pattern of chicken pox was seen with clustering of cases between mid-February to mid-April (spring season) with two peaks – one in February and another in April, when monthly average temperature, total rainfall and humidity all were at their optimum. The peak incidences of chicken pox cases during the spring both in 2018 and 2019 as correlated with climatic data of the same period, it is seen that the prevailing weather then was optimum-average temperature was 23°C, average precipitation was 20-25% of the total annual precipitation and relative humidity was around 65%.Conclusion: The study concluded that majority of the varicella cases occur under ten years of age and boys are a little more susceptible to have the infection than the girls. A seasonal pattern of chicken pox is clearly seen with clustering of cases between mid-February to mid-April (spring season) with two peaks when monthly average temperature, total rainfall and humidity all are optimally favorable for the multiplication of varicella zoster virus.Ibrahim Card Med J 2020; 10 (1&2): 11-17